(untitled) (Journal of Academic Research, 2024)
Abstract This study investigated the effect of using alternative assessment methods on EFL students’ test performance and their attitudes towards these methods. The study was conducted at a secondary school in Misurata, Libya. A quasi-experimental design was employed, involving a control group and an experimental group. The researchers administered a pretest in a traditional pen-and-paper format to minimize potential heterogeneity between the study groups. The experimental group was taught using alternative assessment methods, while the control group was taught using traditional assessment methods. A post-test was administered to both groups to measure their test performance. Additionally, a questionnaire was used to explore students’ attitudes about alternative assessment methods. The study found that the use of alternative assessment (AA) methods did not significantly impact students’ test performance compared to traditional assessment (TA) methods. However, students generally held positive attitudes towards both AA and TA approaches, with a slight preference for AA methods. These results suggest that while AA approaches may not necessarily improve test scores, students view them favorably and tend to prefer them over traditional assessment techniques. Keywords: Alternative assessment, EFL students, Test performance, Attitudes